Use of organic acids for control of Clostridium perfringens in cooked vacuum-packaged ground beef products subjected to substandard cooling procedures - Sabah, J.R.; Harshavardhan, T.; Marsden, James L.; Fung, Daniel Y. C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study determined the ability of Clostridium perfringens spores to germinate and grow after different organic acid treatments in vacuum packaged cooked ground beef subjected to substandard (slow) cooling. Meat samples were inoculated with a three-strain cocktail of C. perfringens spores (ATCC 10388, NCTC 8238, and NCTC 8239), then vacuum-packaged, cooked in a water bath to 167°F internal temperature, and held 20 min. The water bath temperature was then lowered to 130°F, and samples were cooled from 130°F to 45°F over 18 hr. Samples were taken after inoculation, after cooking, and after cooling. In the event of substandard cooling, sodium citrate at 2 or 4.8% or sodium lactate at 4.8% will control C. perfringens growth, with 4.8% sodium citrate showing the best inhibition.
Keywords: Beef; Clostridium perfringens; Cooked ground beef; Organic acids